Peran Organisasi Persatuan Islam Tionghoa Indonesia (Piti) dalam Perkembangan Muslim Tionghoa di Kota Medan Tahun 1998-2023 - Anna Maharani Br Lubis; Sori Monang; M. Nasihudin Ali (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Chinese Islamic Unity Organization (PITI) is a social missionary organization that houses ethnic Chinese Muslims in the city of Medan which was founded in 1961. In its organizational development it experienced obstacles such as during the New Order era when it had to change the name of its organization. And in 1998, PITI Medan could be said to have "a name but no form", in the sense that the PITI Medan organization existed but in all its activities experienced stagnation. However, running an organization does not mean it does not meet obstacles. Currently, PITI Medan is experiencing a decline in organizational activity due to a lack of awareness among the management and members to advance the organization. Due to work and long distances as well as lack of funds, this has also become an obstacle to the development of the PITI Medan organization. Apart from that, due to the Covid-19 pandemic, there have been no activities carried out by the PITI Medan organization until now. The PITI organization has a role as a forum for fostering religion and uniting Chinese Muslims with native Muslims, and native Muslims with ethnic Chinese which is one of the developments of Chinese Muslims in the city of Medan which is realized through activity programs, such as recitations, Muslimat taklim majlis, activities at the month of Ramadan, as well as activities to commemorate Islamic holidays. Keywords: ,